2016
DOI: 10.18203/2394-6040.ijcmph20162574
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of patient's satisfaction regarding the service quality of a rural hospital of Burdwan district, West Bengal, India

Abstract: Background: Patients satisfaction is the basis of quality healthcare services. To improve quality of healthcare it is most important to obtain feedback from patients. Patients' satisfaction or service quality mostly depends on patients' expectation. This study was conducted to identify some important areas where improvement can be done by knowing patients expectation, perception and their gaps. Methods: A cross-sectional study was conducted among patients aged >18 years. Total 350 patients from OPD by consecut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 2 publications
(8 reference statements)
0
6
0
Order By: Relevance
“…Empathy dimension is the dimension of the lowest levels of satisfaction in rural areas, it also needs to be a concern, where the ability of doctors to provide care to patients, care and friendliness on patients need to be improved. It is revealed that the physician has the most important role in the improvement of service satisfaction (Ibrahima, 2016;Naskar et al, 2016, Singh et al, 2016.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Empathy dimension is the dimension of the lowest levels of satisfaction in rural areas, it also needs to be a concern, where the ability of doctors to provide care to patients, care and friendliness on patients need to be improved. It is revealed that the physician has the most important role in the improvement of service satisfaction (Ibrahima, 2016;Naskar et al, 2016, Singh et al, 2016.…”
Section: Resultsmentioning
confidence: 99%
“…Patient satisfaction with health services describe the level where the needs of patients "In line with expectations and provide a standard of service that is acceptable". Several factors have been shown to affect patient satisfaction with the services of his/her teeth namely "technical skills, interpersonal factors, patient comfort, cost, and facilities" (Balkaran et al, 2014;Naskar P et al, 2016). The main factor of satisfaction is the quality of health care provided hospital car, processes of care and outcomes of care.…”
Section: Introductionmentioning
confidence: 99%
“…The patients want trained officers and provide them with information they might needed. Therefore, to ensure optimal quality of service, health care providers should be aware of and sensitive to patient satisfaction because it is one factor that can help to improve the outcome of treatment provided [8] [11].…”
Section: Discussionmentioning
confidence: 99%
“…Most complaints of patients in a satisfaction survey concerning the presence of officers who are not professional in providing health services, which are still audible complaint would be the clerk unfriendly and indifferent to patient complaints. The most prominent factor is the quality of service; treatment time is long, long waiting times and outcomes of care were less than satisfactory [4][7] [8].…”
Section: Introductionmentioning
confidence: 99%
“…Patient satisfaction has been recognized as the most important key success indicator in the healthcare industry [36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52]. It is linked to the concepts of perceptions and expectations [33].…”
Section: Patient Satisfaction Of Healthcare Organization Employed Witmentioning
confidence: 99%